2013
DOI: 10.5539/jas.v5n2p227
|View full text |Cite
|
Sign up to set email alerts
|

Forage Yield, Chemical Composition and In Vitro Gas Production of Triticale (X Triticosecale wittmack) and Barley (Hordeum vulgare) asociated with Common Vetch (Vicia sativa) Preserved as Hay or Silage

Abstract: Forage cereals are deficient in protein, but legumes are acceptable in protein quality; the association of both forages can increase their nutritional value and biomass production. The objectives were to evaluate forage yield, chemical composition, energy content and In Vitro gas production of varieties of triticale (UAEMex and Siglo XXI), barley (Doña Josefa) and its association with common vetch, harvested at 145 days (milky-dough stage); a portion was ensiled and the other was hayed. Data were analyzed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(28 reference statements)
0
1
2
Order By: Relevance
“…Consequently, it can be stated that the increasing ADF levels in feed causes a decrease in the total digestibility of feeds (Lithourgidis et al 2006) and in the event of this increasing beyond a certain level, an energy loss occurs depending on the increase in methane production (Tekce and Gul, 2014). It is reported that IVDMD of barley forage is 61.7% (Hervas et al 2004) and 66.4% (Aguilar-Lopez et al 2013). While the IVDMD values obtained from all harvesting periods in the study are found to be higher compared to values obtained by other researchers, the IVOMD level of barley determined by Kowalski et al (2014) was 72.6%.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…Consequently, it can be stated that the increasing ADF levels in feed causes a decrease in the total digestibility of feeds (Lithourgidis et al 2006) and in the event of this increasing beyond a certain level, an energy loss occurs depending on the increase in methane production (Tekce and Gul, 2014). It is reported that IVDMD of barley forage is 61.7% (Hervas et al 2004) and 66.4% (Aguilar-Lopez et al 2013). While the IVDMD values obtained from all harvesting periods in the study are found to be higher compared to values obtained by other researchers, the IVOMD level of barley determined by Kowalski et al (2014) was 72.6%.…”
Section: Resultscontrasting
confidence: 62%
“…It is reported that the ME and NE L levels of barley forage are 9.8 MJ/kg DM and 5.6 MJ/kg DM, respectively (Canbolat, 2012). In another study, the NE L level of barley harvested at the heading stage is 1.5 Mcal/kg DM and this value is the lowest level obtained from all harvests in the study (Aguilar-Lopez et al 2013).…”
Section: Resultsmentioning
confidence: 74%
“…IVOMD in BKO was similar to work by David et al (2010), who reported values ranging from 601 to 694 g kg −1 DM for different varieties of BKO at the same growth stage. However, IVOMD for BLY were lower than reports by Aguilar-López et al (2013) in Mexico and Benchaar et al (2014) in Canada.…”
Section: Discussioncontrasting
confidence: 59%